The intelligent camera: images of computer vision. - Grimson, W E (1993)
The field of computer vision is concerned with the problem of deducing properties of object surfaces and the position and orientation of objects in scenes. I illustrate the fundamental difficulty of the problem, describe common approaches taken in the field, and provide representative examples of current solutions.